Long-term sevoflurane exposure resulted in temporary rather than lasting cognitive impairment in Drosophila - Liu, Ziming; Pan, Xuanyi; Guo, Jiguang; Li, Liping; Tang, Yuxin; Wu, Guangyi; Li, Ming; Wang, Hongjie (Behavioural brain research, 2023)
Sevoflurane is the primary inhaled anesthetic used in pediatric surgery. It has been the focus of research since animal models studies found that it was neurotoxic to the developing brain two decades ago. However, whether pediatric general anesthesia can lead to permanent cognitive deficits remained a subject of heated debate. Therefore, our study aims to determine the lifetime neurotoxicity of early long-time sevoflurane exposure using a short-life-cycle animal model, Drosophila melanogaster. To investigate this question, we measured the lifetime changes of two-day-old flies' learning and memory abilities after anesthesia with 3 % sevoflurane for 6 h by the T-maze memory assay. We evaluated the apoptosis, levels of ATP and ROS, and related genes in the fly head. Our results suggest that 6 h 3 % sevoflurane exposure at a young age can only induce transient neuroapoptosis and cognitive deficits around the first week after anesthesia. But this brain damage recedes with time and vanishes in late life. We also found that the mRNA level of caspases and Bcl-2, ROS level, and ATP level increased during this temporary neuroapoptosis process. And mRNA levels of antioxidants, such as SOD2 and CAT, increased and decreased simultaneously with the rise and fall of the ROS level, indicating a possible contribution to the recovery from the sevoflurane impairment. In conclusion, our results suggest that one early prolonged sevoflurane-based general anesthesia can induce neuroapoptosis and learning and memory deficit transiently but not permanently in Drosophila.